VAT Reforms and Sectoral Financial Performance in Nigeria: A Panel Data Analysis - Mohammed Aminu Bello (Yayasan Sinergi Kawula Muda, 2025)
This study investigates the impact of Value Added Tax (VAT) reforms on sectoral financial performance in Nigeria, focusing on how recent changes in VAT policy—such as rate increases, digital enforcement, and administrative restructuring—have affected key sectors including telecommunications, manufacturing, retail, and agriculture. The relevance of the study lies in the growing need for efficient tax systems in revenue-dependent developing economies and the limited empirical evidence on how VAT reforms influence financial outcomes across heterogeneous sectors. Drawing on panel data from 2011 to 2020, the research employs a fixed-effects regression approach, incorporating a composite index of VAT reform constructed via principal component analysis. Sectoral financial performance is assessed using return on assets (ROA) and profit margin as key indicators. The results reveal that VAT reforms have a significant but uneven effect on financial performance across sectors. Formal, technology-enabled sectors such as telecommunications and manufacturing experienced improved financial outcomes, driven by stronger compliance and institutional capacity. In contrast, informal and agrarian sectors faced barriers in adapting to the reforms, primarily due to limited digital readiness and compliance constraints. The findings suggest that VAT reforms are not universally effective and must be tailored to sector-specific conditions. Policy recommendations include enhancing digital infrastructure, strengthening sectoral tax education, and designing adaptive compliance mechanisms to promote inclusive and sustainable fiscal outcomes. These insights contribute to a nuanced understanding of tax reform efficacy in structurally diverse developing economies.